Gag p24 Is a Marker of Human Immunodeficiency Virus Expression in Tissues and Correlates With Immune Response. (9th March 2021) - Wu, Guoxin; Zuck, Paul; Goh, Shih Lin; Milush, Jeffrey M; Vohra, Poonam; Wong, Joseph K; Somsouk, Ma; Yukl, Steven A; Shacklett, Barbara L; Chomont, Nicolas; Haase, Ashley T; Hatano, Hiroyu; et al.
Abstract: We demonstrate that human immunodeficiency virus (HIV) gag p24 protein is more readily detected in gut and lymph node tissues than in blood CD4 + T cells and correlates better with CD4 count during antiretroviral therapy (ART). Gut p24 levels also measurably decline with ART in natural controllers. During ART, gut p24 expression is more strongly associated both with HIV-specific CD8 + T-cell frequency and plasma soluble CD14 levels than gut HIV RNA expression. This study supports using gag p24 as a marker of HIV expression in HIV + tissues to study effects of viral persistence and to monitor efficacy of treatment in HIV-based clearance studies. Abstract : Continuous expression of HIV protein in lymphoid tissues despite prolonged viral suppression helps explain persistent immune activation and HIV-specific T-cell responses. Measuring HIV protein in tissues will likely be important for understanding mechanisms of persistence and evaluating future cure approaches.